Microclimatic variation of thermal comfort in a district of Lisbon (Telheiras) at night - Andrade, Henrique (2019)
The microclimatic spatial variation of air temperature, wind speed, radiative fluxes and Physiological Equivalent Temperature (PET) was studied in Telheiras, a northern district of the city of Lisbon. The main goal was to assess how to improve outdoor thermal conditions based on research results. An empirical model was developed to estimate PET in Telheiras under different weather types; the model allows the continuous spatial representation of PET, using a Geographical Information System (GIS) and can be used in other areas of Lisbon. Although there is a small microclimatic variation in air temperature, the PET presents a much stronger variation, due to the influence of wind and radiative fluxes. Urban geometry, expressed by the Sky View Factor (SVF), is the main factor controlling the microclimatic diversity of the neighbourhood. The coolest conditions occur in open areas (centre of large courtyards and marginal areas) and the warmest in streets with low SVF that are sheltered from the wind.